Combinatorial biosynthesis and the basis for substrate promiscuity in class I diterpene synthases - Jia, Meirong (Metab Eng, 2019)
Terpene synthases are capable of mediating complex reactions, but fundamentally simply catalyze lysis of allylic diphosphate esters with subsequent deprotonation. Even with the initially generated tertiary carbocation this offers a variety of product outcomes, and deprotonation further can be preceded by the addition of water. This is particularly evident with labdane-related diterpenes (LRDs) where such lysis follows bicyclization catalyzed by class II diterpene cyclases (DTCs) that generates preceding structural variation. Previous investigation revealed that two diterpene synthases (DTSs), one bacterial and the other plant-derived, exhibit extreme substrate promiscuity, but yet still typically produce exo-ene or tertiary alcohol LRD derivatives, respectively (i.e., demonstrating high catalytic specificity), enabling rational combinatorial biosynthesis. Here two DTSs that produce either cis or trans endo-ene LRD derivatives, also plant and bacterial (respectively), were examined for their potential analogous utility. Only the bacterial trans-endo-ene forming DTS was found to exhibit significant substrate promiscuity (with moderate catalytic specificity). This further led to investigation of the basis for substrate promiscuity, which was found to be more closely correlated with phylogenetic origin than reaction complexity. Specifically, bacterial DTSs exhibited significantly more substrate promiscuity than those from plants, presumably reflecting their distinct evolutionary context. In particular, plants typically have heavily elaborated LRD metabolism, in contrast to the rarity of such natural products in bacteria, and the lack of potential substrates presumably alleviates selective pressure against such promiscuity. Regardless of such speculation, this work provides novel biosynthetic access to almost 19 LRDs, demonstrating the power of the combinatorial approach taken here.